2018
DOI: 10.1002/aoc.4405
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic and structural study of complexation of phenylboronic acid with salicylhydroxamic acid and related ligands

Abstract: Stability constants of boronate complexes with a highly efficient bioconjugation ligand salicylhydroxamic acid, its derivatives and some structurally related compounds were determined by potentiometric and spectroscopic titrations at variable pH allowing one to obtain detailed stability – pH profiles and to identify the optimum pH for complexation with each ligand. The N,O‐binding of salicylhydroxamic acid via condensation of boronic acid with phenolic OH and hydroxamic NH groups was established by crystal str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 60 publications
0
6
0
Order By: Relevance
“…The hydroxamic acids L 1 –L 3 were prepared according to the literature procedures (as detailed in the Supporting Information). The attempts to prepare di-hydroxamic acid L 4 were unsuccessful.…”
Section: Methodsmentioning
confidence: 99%
“…The hydroxamic acids L 1 –L 3 were prepared according to the literature procedures (as detailed in the Supporting Information). The attempts to prepare di-hydroxamic acid L 4 were unsuccessful.…”
Section: Methodsmentioning
confidence: 99%
“…A more recent study reported the binding constants of several PBA/SHA derivative pairs. 113 Among the different SHA derivatives tested (i.e., SHA, N-methyl-SHA, ortho-hydroxyl-SHA, and 2,5-dihydroxy-1,4-benzdihydroxamic acid), SHA and ortho-hydroxyl-SHA had the highest K eq values at physiological pH (1.6 × 10 4 and 3.6 × 10 4 M −1 , respectively), making them interesting candidates for BE cross-linking. To date, a single hydrogel system based on PBA/SHA cross-linking has been reported.…”
Section: New Perspectives In Boronate Ester Hydrogel Designmentioning
confidence: 98%
“…Perhaps, the reaction of BA with salicylhydroxamic acids (SHA) has garnered the most attention besides that of boronate ester formation with diols. Discovered by Stolowitz and co-workers 63 in 2001, it has been applied extensively, and a detailed thermodynamic study was reported by Martínez-Aguirre et al 64 in 2018. With an association constant of 10 4 M −1 at pH 7.4 for the complex of phenylboronic acid (PBA) and SHA, the complex is stable at physiological pH, undergoing possible hydrolysis at pH < 5 ( Fig.…”
Section: Salicylhydroxamic–boronate (Shab) Conjugatementioning
confidence: 99%